Grain boundary engineering parameters for ultrafine grained microstructures: Proof of principles by a systematic composition variation in the Cu-Ni system. (15th May 2018) - Emeis, Friederike; Peterlechner, Martin; Divinski, Sergiy V.; Wilde, Gerhard
Abstract: The main principles of grain boundary engineering of an ultrafine grained microstructure are studied via a systematic variation of the stacking fault energy ( γ S F E ), solid solution effects (SSEs) and the homologous deformation/annealing temperatures choosing the Cu-Ni system as a model case for non-segregating alloys. Cu and Ni are completely miscible and the γ S F E varies strongly with the alloy composition. Ultrafine grained microstructures are produced by high-pressure torsion and their evolution upon annealing is investigated. The thermal stability and the saturation grain sizes after deformation are determined by SSEs. The fraction of deformation twins varies in accordance with the γ S F E . The increase of the length fraction of Σ 3 grain boundaries versus the grain size is found to be governed by the SSEs, whereas the increase of the length fraction of Σ 9 grain boundaries versus the grain size depends on the γ S F E . The results indicate that grain boundary engineering may lead to an optimum ultrafine grained structure, i.e. with a high length fraction of Σ 3 and Σ 9 grain boundaries of approximately 40%. This is a significantly large fraction in comparison to a not-engineered microstructure and achieved for grain sizes below 1000 nm in alloys close to the equiatomic composition having a low γ S F E and a high melting temperature. This high fraction of Σ 3 n grain boundaries (including their conjunctions) proved itself most effective for microstructure stabilization in this virtually non-segregating system. Thus, for Cu50 Ni50 and Cu65 Ni35, a narrow grain size distribution of small grains, a high hardness and a high fraction of special grain boundaries can be adjusted. Graphical abstract: Image 1